Blood Beta-Amyloid and Tau in Down Syndrome: A Comparison with Alzheimer’s Disease - Lee, Ni-Chung; Yang, Shieh-Yueh; Chieh, Jen-Jie; Huang, Po-Tsang; Chang, Lih-Maan; Chiu, Yen-Nan; Huang, Ai-Chiu; Chien, Yin-Hsiu; Hwu, Wuh-Liang; Chiu, Ming-Jang (Frontiers in Aging Neuroscience, 2017)
Background: Changes in beta-amyloids and tau proteins have been noted in patients with Alzheimer’s disease (AD) and patients with both Down syndrome (DS) and AD. However, reports of changes in the early stage of regression, such as behavioral and psychological symptoms of dementia (BPSD), in DS are sparse. Methods: Seventy-eight controls, 62 patients with AD, 35 with DS, and 16 with DS with degeneration (DS_D), including 9 with BPSD and 7 with dementia, were enrolled. The levels of beta-amyloids 40 and 42 (Abeta-40, Abeta-42) and tau protein in the blood were analyzed using immunomagnetic reduction. The Adaptive Behavior Dementia Questionnaire (ABDQ) was used to evaluate the clinical status of the degeneration. Results: The Abeta-40 and tau levels were higher and the Abeta-42 level and Abeta-42/Abeta-40 ratio were lower in DS than in the controls (all p < 0.001). Decreased Abeta-40 and increased Abeta-42 levels and Abeta-42/40 ratios were observed in DS_D compared with DS without degeneration (all p < 0.001). The ABDQ score was negatively correlated with the Abeta-40 level (rho= -0.556) and the tau protein level (rho= -0.410) and positively associated with the Abeta-42 level (rho= 0.621) and the Abeta-42/40 ratio (rho= 0.544) (all p < 0.05). Conclusions: The Abeta-40 and Abeta-42 levels and the Abeta-42/Abeta-40 ratio are considered possible biomarkers for the early detection of degeneration in DS. The elevated Abeta-40 and tau levels in DS may indicate early neurodegeneration. The increased Abeta-42 in DS_D may reflect the neurotoxicity of Abeta-42. The paradox of the tau decreases in DS_D could be explained by a burnout phenomenon during long-term neurodegeneration. The different patterns of the plasma beta amyloids and tau protein may imply a different pathogenesis between Down syndrome with degeneration and Alzheimer’s disease in the general population, in spite of their common key pathological features.